2019
DOI: 10.1159/000497281
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on Microsurgical Denervation of Spermatic Cord for Refractory Chronic Orchialgia

Abstract: Objectives: Microsurgical denervation of the spermatic cord (MDSC) is a treatment option for chronic orchialgia (CO) refractory to conservative treatment. Studies showed specific nerve fibers as the possible cause of CO. We aimed to present the outcomes of ligation of these nerves using targeted MDSC. Methods: We retrospectively reviewed 30 cases who underwent targeted MDSC from August 2014 to February 2018. Patients included were under strict criteria. Pain was assessed preoperatively and postoperatively usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Thus, 34 studies were included in this systemic review; six prospective, 21 retrospective and seven case series. Most studies reported the results of microsurgical spermatic cord denervation (MSCD) (n = 19) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], while the remaining studies investigated the impact of various nerve-blocking techniques (n = 8) [28][29][30][31][32][33][34][35], vasectomy reversal (n = 5) [36][37][38][39][40], and extirpative surgery (n = 2) [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 34 studies were included in this systemic review; six prospective, 21 retrospective and seven case series. Most studies reported the results of microsurgical spermatic cord denervation (MSCD) (n = 19) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], while the remaining studies investigated the impact of various nerve-blocking techniques (n = 8) [28][29][30][31][32][33][34][35], vasectomy reversal (n = 5) [36][37][38][39][40], and extirpative surgery (n = 2) [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The present review identified 19 individual studies including 1676 testicular units for which MSCD was performed. In most cases an open approach for surgery was performed (inguinal [n = 14]; subinguinal [n = 3]; Table 1) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Depending on the level of the incision, the aponeurosis of the external oblique muscle is either spared or opened.…”
Section: Microsurgical Spermatic Cord Denervationmentioning
confidence: 99%
“…It is important to try and identify such patients that will not do well post-SVE. One study suggest a spermatic cord block may be beneficial in pre-procedural assessment, in the setting of an inguinal hernia repair or vasectomy who present with a varicocele and pain 29 . Spermatic cord block with a long acting local anaesthetic agent may aid in diagnosing neuropathic pain in addition to providing guidance as to the type of intervention that may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatic cord block with a long acting local anaesthetic agent may aid in diagnosing neuropathic pain in addition to providing guidance as to the type of intervention that may be warranted. For example, if a patient has a greater than 50% reduction in pain after spermatic cord block, microsurgical cord denervation may be an effective treatment option 29 .…”
Section: Discussionmentioning
confidence: 99%